Motivational Factors and Level of Satisfaction in the Implementation of School-Based Management and its Effect to Teachers’ Performance - Abio, Kem Berly Canoy (International Journal of Research in Interdisciplinary Studies, 2026)
This study intended to investigate the motivational factors and their relationship to teachers’ job performance as well as the actual satisfaction of the stakeholders in the implementation of school-based management influence teachers’ performance. Specifically, it sought to answer the extent that the teachers are motivated by the motivational factors in terms of the existence needs, relatedness needs and growth needs. The study also aimed to gather data from the teachers’ latest RPMS rating as basis for the teachers’ performance and the level of satisfaction of the teachers in the implementation of School- Based Management of the school in terms of Leadership and Governance, Curriculum and Instruction, Accountability and Continuous Improvement and Management of Resources and to examine the significant relationship between the motivational factors and level of satisfaction in the implementation of SBM and the teachers’ performance. A convenience research design was utilized, involving 250 public elementary school teachers. The researchers adopted a questionnaire that underwent validity and reliability testing. Data were analyzed using descriptive statistics such as mean, standard deviation, and Pearson r. The study concluded the higher is teachers’ motivation and positive governance, the better is their performance.